Utilization of the Planner 5D for the Design of a Medical Record Room at the Pesantren 1 Public Health Center - Putri Indra Suryandari; Cici Nila Ardila; Krisnita Dwi Jayanti; Ratna Frenty Nurkhalim; Andra Dwitama Hidayat; Dinda Agnes Wahyu Aprilia; Rany Eka Putranti; Raya Mulyasari (Politeknik Negeri Jember, 2023)
A good design plan needs to be considered in the spatial arrangement of health service facilities. The Pesantren 1 Community Health Center plans to build an ergonomic medical record room. Creating or designing an ergonomic space requires knowledge of human anthropometry, work requirements, tool design, facilities used, methods, physical and psychological work schedules, and aesthetics. Many room designers have created designs that go beyond 2 dimensions. Planner 5D is an application that can assist users in designing a room. Planner 5D lets you easily create 3D designs from any angle. The purpose of this research is to design a medical record room using the Planner 5D application. Researchers used qualitative methods to collect information by interviewing medical record officers as the main informants and the head of the Community Health Center as key informant or triangular informant. The results of this study are the number of human resources needed, the number of infrastructure needs, circulation analysis of space for movement, and the layout of medical records designed by considering the anthropometry of officers. In conclusion, designing using the Planner 5D application is easy to implement. Because of the many features that are presented, the thing that needs to be considered in making layouts with this application is that in selecting furniture it is necessary to pay attention to the user's anthropometry.